Omics-Driven Biomarkers of Psoriasis: Recent Insights, Current Challenges, and Future Prospects - Aydin B; Arga KY; Karadag AS (Dove Medical Press, 2020)
Busra Aydin,1 Kazim Yalcin Arga,1 Ayse Serap Karadag2 1Department of Bioengineering, Faculty of Engineering, Marmara University, Istanbul, Turkey; 2Department of Dermatology, Istanbul Medeniyet University, School of Medicine, Goztepe Research and Training Hospital, Istanbul, TurkeyCorrespondence: Ayse Serap KaradagDepartment of Dermatology, Istanbul Medeniyet University, School of Medicine, Goztepe Research and Training Hospital, Istanbul, TurkeyTel +90 5336552260Fax +90 216 566 66 14Email karadagaserap@gmail.comAbstract: Advances in omics technologies have made it possible to unravel biomarkers from different biological levels. Intensive studies have been carried out to uncover the dysregulations in psoriasis and to identify molecular signatures associated with the pathogenesis of psoriasis. In this review, we presented an overview of the current status of the omics-driven biomarker research and emphasized the transcriptomic, epigenomic, proteomic, metabolomic, and glycomic signatures proposed as psoriasis biomarkers. Furthermore, insights on the limitations and future directions of the current biomarker discovery strategies were discussed, which will continue to comprehend broader visions of psoriasis research, diagnosis, and therapy especially in the context of personalized medicine.Keywords: psoriasis, biomarker, omics, inflammatory skin diseases, personalized medicine, psoriasis biomarkers, omics biomarkers